Skin xenotransplantation: technological advances and future directions. Issue 5 (October 2020) - Kalsi, Richa; Messner, Franka; Brandacher, Gerald
Abstract : Purpose of review: To summarize the evolution of skin xenotransplantation and contextualize technological advances and the status of clinically applicable large animal research as well as prospects for translation of this work as a viable future treatment option. Recent findings: Porcine xenografts at the start of the millennium were merely biologic dressings subject to rapid rejection. Since then, numerous important advances in swine to nonhuman primate models have yielded xenotransplant products at the point of clinical translation. Critical genetic modifications in swine from a designated pathogen-free donor herd have allowed xenograft survival reaching 30 days without preconditioning or maintenance immunosuppression. Further, xenograft coverage appears not to sensitize the recipient to subsequent allograft placement and vice versa, allowing for temporary coverage times to be doubled using both xeno and allografts. Summary: Studies in large animal models have led to significant progress in the creation of living, functional skin xenotransplants with clinically relevant shelf-lives to improve the management of patients with extensive burns.